Waste Solanum melongena stem extract for corrosion inhibition of mild steel in 1M NaCl - Maurya S.; Jaiswal A.; Ji G.; Prakash R. (My University, 2025)
Corrosion of metals is a serious problem for the economy and human lives of any country. Several researchers have been working to minimize the loss of corrosion damage. Green corrosion inhibitors (GCI) are a simple solution of the corrosion problem since GCI is non- toxic, efficient in corrosion inhibition, biodegradable and available at low cost. In this regard waste natural materials (WNM) have attracted a great attention of the scientists since their use as corrosion inhibitors is economic, safe and eco-friendly (recycling of the waste). In this work, Solanum melongena steam (brinjal cap) aqueous extract (SMSAE) is used for corrosion inhibition of low carbon steel (LCS) in 1 M NaCl. The extract is characterized by Uv-visible and FTIR spectroscopy, which suggest that the extract is electrochemical active. The corrosion inhibition properties of the extract was determined by weight loss measurements, electrochemical impedance spectroscopy (EIS), open circuit potential (OCP) curves and Tafel polarization curves (TPC). The results show that the extract is giving inhibition efficiency > 70% at 500 mg L-1of the extract. Surface and compositional analysis was performed by Scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy, which evidently illustrate that the extract is successfully inhibiting corrosion of mild steel in 1 M NaCl. It can be said based on results that SMSAE (WNM) is providing good inhibition efficiency and can be used in different applications. © 2021 Elsevier Ltd. All rights reserved.